Analisis Kritis terhadap Strategi Misi Kontekstualisasi Paulus dalam 1 Korintus 9:20 bagi Tantangan Penginjilan di Era Postmodern - Obehetan, Yeheskiel; Rompis, Febrianto Sutomo (JURNAL LUXNOS, 2025)
The purpose of this study is to critically analyse Paul's contextualization of evangelism based on 1 Corinthians 9:20. This purpose is motivated by the diverse approaches to contextualization that have developed widely in the postmodern era. This study uses a qualitative method with a literature review approach. The results of the study show that: First, Paul's contextualization is still relevant in the postmodern era. Second, Paul's contextualization always has biblical limitations. Third, Paul's contextualization is oriented towards the salvation of souls. A comprehensive and holistic understanding of Paul's contextual evangelism enables evangelists to implement it within biblical boundaries in their evangelistic ministry so that the Gospel message can be conveyed and win as many people as possible in the postmodern era.